1986
DOI: 10.1056/nejm198604173141601
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine in the Prevention and Treatment of the Amyloidosis of Familial Mediterranean Fever

Abstract: To determine whether colchicine prevents or ameliorates amyloidosis in patients with familial Mediterranean fever, we followed 1070 patients with the latter disease for 4 to 11 years after they were advised to take colchicine to prevent febrile attacks. Overall, at the end of the study, the prevalence of nephropathy was one third of that in a study conducted before colchicine was used to treat familial Mediterranean fever. Among 960 patients who initially had no evidence of amyloidosis, proteinuria appeared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
207
1
24

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 610 publications
(236 citation statements)
references
References 16 publications
4
207
1
24
Order By: Relevance
“…The joint involvement subsides within days, however in about 5% of patients destructive arthritis involving mainly the large joints many ensue [22]. The mainstay medication for treatment of FMF and amyloidosis prophylaxis is colchicine at a dose of 1.5-2mg daily [23,24]. However, in 5 to 15% of patients treatment fails and they get labeled as non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…The joint involvement subsides within days, however in about 5% of patients destructive arthritis involving mainly the large joints many ensue [22]. The mainstay medication for treatment of FMF and amyloidosis prophylaxis is colchicine at a dose of 1.5-2mg daily [23,24]. However, in 5 to 15% of patients treatment fails and they get labeled as non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…4,8 With a presence of amyloidosis, approximately 20% percent of patients had nephrotic range proteinuria and renal functions were deteriorated in all of these patients with nephrotic syndrome. 4 In patients who have non-nephrotic proteinuria, improvement of proteinuria reported approximately in 6% and stabilization in 79%. 4 In our study, decreasing of proteinuria higher than 50% was defined approximately in 80% of patients with non-nephrotic proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…4 In patients who have non-nephrotic proteinuria, improvement of proteinuria reported approximately in 6% and stabilization in 79%. 4 In our study, decreasing of proteinuria higher than 50% was defined approximately in 80% of patients with non-nephrotic proteinuria. Our study revealed that, colchicine treatment reduced proteinuria in half of the patients with nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of this disease is often difficult, because there are few specific therapies available. However, it has been reported that the prognosis of amyloidosis can be improved by appropriate early treatment, for example using melphalan (15), colchicine (15,16), and 4'-iodo-4'-deoxydoxorubicin (17). Thus, there has been a growing demand for the development of a specific noninyasive diagnostic technique.…”
Section: Discussionmentioning
confidence: 99%